Trinidad. Coco-Nut cracking - (:unkn) unknown (My University, 2009)
A picture of a man cracking open the coconuts to extract the dried copra found inside.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Coconut palm; Agriculture; Working class